KEPASTIAN HUKUM CYBER NOTARY DALAM KAEDAH PEMBUATAN AKTA NOTARIS DAN PPAT TERKAIT BERHADAPAN OLEH PARA PIHAK - Ramalus, Alex (PT. Hafasy Dwi Nawasena, 2023)
Indonesia is a state of law with a form of state government contained in the 1945 Constitution. This concept was born from the struggle of the Indonesian people to break away from the entanglement and arbitrary actions of the authorities. Globalization encourages cultural, economic, social and legal developments that become the basis of thought for all parties involved. The most obvious current of globalization is the rapid development of information technology known as the Digitalization 4.0 Era. This is supported by the ease of accessing information via the internet. The development of information and communication technology cannot be separated from the concept that humans are social creatures. The process of managing conventional legal products that can only be accessed offline can now be done online, known as cyber notary. The research method used is normative juridical research. The research was conducted by examining theories, concepts and laws and regulations related to the research. Until now there is no specific law governing cyber notary in Indonesia. The establishment of a special law on cyber notary is needed to provide legal certainty in the implementation of cyber notary, so that it has a stronger evidentiary value as an authentic deed. The implementation of Cyber notary can be facilitated by electronic signatures or fingerprints to create an authentic deed